Lower fatigue and faster recovery of ultra-short race pace swimming training sessions - Cuenca-Fernández, F.; Boullosa, D.; Ruiz-Navarro, J. J.; Gay, A.; Morales-Ortíz, E.; López-Contreras, G.; Arellano, R. (Research in Sports Medicine, 2023)
Ultra-short race-pace training (USRPT) is a high-intensity training modality used in swimming for the development of specific race-technique. However, there is little information about the fatigue associated to this modality. In a crossover design, acute responses of two volume-equated sessions (1000-m) were compared on 14 national swimmers: i) USRPT: 20×50-m; ii) RPT: 10×100-m. Both protocols followed an equivalent work-recovery ratio (1:1) based on individual 200-m race-pace. The swimming times and the arm-strokes count were monitored on each set and compared by mixed-models. Blood lactate [La-] and countermovement jump-height (CMJ) were compared within and between conditions 2 and 5 min after the protocols. The last bouts in RPT were 1.5-3% slower than the target pace, entailing an arm-strokes increase of ~0.22 for every second increase in swimming time. USRPT produced lower [La-] ([Mean ± standard deviation], 2 min: 8.2±2.4 [p = 0.021]; 5 min: 6.9±2.8 mM/L [p = 0.008]), than RPT (2 min: 10.9±2.3; 5 min: 9.9±2.4 mM/L). CMJ was lowered at min 2 after RPT (-11.09%) and USRPT (-5.89%), but returned to baseline in USRPT at min 5 of recovery (4.07%). In conclusion, lower fatigue and better recovery were achieved during USRPT compared to traditional high-volume set.